Adult Patient with Synchronous Gastrointestinal Stromal Tumor and Xp11 Translocation-Associated Renal Cell Carcinoma: A Unique Case Presentation with Discussion and Review of Literature - Vanda Farahmand Torous; Albert Su; David Y. Lu; Sarah M. Dry (Case Reports in Urology)
Gastrointestinal stromal tumor (GIST) is the most common primary mesenchymal tumor of the gastrointestinal tract. This entity comprises a wide spectrum of tumors that vary from benign to overtly malignant, with the majority of these tumors harboring oncogenic mutations of the KIT receptor tyrosine kinase that can aid in diagnosis as well as in targeted therapy. Although the majority of GISTs are sporadic, there are forms that are associated with a variety of syndromes including Carney-Stratakis syndrome and neurofibromatosis type 1, as well as a subset of familial GIST syndromes that are caused by germline mutations in KIT or PDGFRA. Here, we describe an unusual case of a patient who was found to have a large abdominal GIST with an incidentally found Xp11 translocation-associated renal carcinoma. The karyotype of the renal carcinoma revealed an unbalanced rearrangement involving an (X;22) translocation at Xp11.2 and 22p11.2, which has not been reported in the literature. Although GISTs have shown an association with other primary malignant neoplasms, including simultaneous presence with unilateral clear cell renal cell carcinoma and bilateral papillary renal cell carcinomas, we describe the first reported case of synchronous GIST and Xp11 translocation-associated renal cell carcinoma.